Cloning and nucleotide sequences of lux genes and characterization of luciferase of Xenorhabdus luminescens from a human wound. - Xi, L (1991)
Xenorhabdus luminescens HW is the only known luminous bacterium isolated from a human (wound) source. A recombinant plasmid was constructed that contained the X. luminescens HW luxA and luxB genes, encoding the luciferase alpha and beta subunits, respectively, as well as luxC, luxD, and a portion of luxE. The nucleotide sequences of these lux genes, organized in the order luxCDABE, were determined, and overexpression of the cloned luciferase genes was achieved in Escherichia coli host cells. The cloned luciferase was indistinguishable from the wild-type enzyme in its in vitro bioluminescence kinetic properties. Contrary to an earlier report, our findings indicate that neither the specific activity nor the size of the alpha (362 amino acid residues, Mr 41,389) and beta (324 amino acid residues, Mr 37,112) subunits of the X. luminescens HW luciferase was unusual among known luminous bacterial systems. Significant sequence homologies of the alpha and beta subunits of the X. luminescens HW luciferase with those of other luminous bacteria were observed. However, the X. luminescens HW luciferase was unusual in the high stability of the 4a-hydroperoxyflavin intermediate and its sensitivity to aldehyde substrate inhibition.